Pushing the envelope: Immune mechanism and application landscape of macrophage-activating lipopeptide-2 - Liao, Daoyong; Su, Xiaoling; Wang, Jingyun; Yu, Jianwei; Luo, Haodang; Tian, Wei; Ye, Zufeng; He, Jun (Frontiers in Immunology, 2023)
Mycoplasma fermentans can cause respiratory diseases, arthritis, genitourinary tract infections, and chronic fatigue syndrome and have been linked to the development of the human immunodeficiency virus. Because mycoplasma lacks a cell wall, its outer membrane lipoproteins are one of the main factors that induce inflammation in the organism and contribute to disease development. Macrophage-activating lipopeptide-2 (MALP-2) modulates the inflammatory response of monocytes/macrophages in a bidirectional fashion, indirectly enhances the cytotoxicity of NK cells, promotes oxidative bursts in neutrophils, upregulates surface markers on lymphocytes, enhances antigen presentation on dendritic cells and induces immune inflammatory responses in sebocytes and mesenchymal cells. MALP-2 is a promising vaccine adjuvant for this application. It also promotes vascular healing and regeneration, accelerates wound and bone healing, suppresses tumors and metastasis, and reduces lung infections and inflammation. MALP-2 has a simple structure, is easy to synthesize, and has promising prospects for clinical application. Therefore, this paper reviews the mechanisms of MALP-2 activation in immune cells, focusing on the application of MALP-2 in animals/humans to provide a basis for the study of pathogenesis in Mycoplasma fermentans and the translation of MALP-2 into clinical applications.